IMPLIKASI ONE CHINA POLICY TERHADAP KEBIJAKAN KEIMIGRASIAN DI INDONESIA - Al Dzikri, Ilham Akbar Dzaky; Dewanto, Rafi Navynanda Kusuma; Pramesti Dewi, Anak Agung Istri Agung Cyntia (Jurnal Ilmiah Kajian Keimigrasian, 2024)
This research aims to analyze the implications of the "One China Policy" on Indonesia's immigration policy. Based on the Republic of Indonesia Law Number 6 of 2011 on Immigration, immigration serves as an important instrument for maintaining state sovereignty and security, as well as a facilitator of community welfare development. The "One China Policy" is China's diplomatic policy asserting that there is only one legitimate government representing all of China, including Taiwan, which also influences Indonesia's diplomatic relations. Although Indonesia does not have formal diplomatic relations with Taiwan, economic, trade, and socio-cultural interactions between the two entities continue. This study examines how the "One China Policy" principle affects Indonesia's immigration policy towards Taiwanese nationals, particularly in the aspects of visas, residency permits, and immigration oversight. By reviewing legislation, immigration practices, and public discourse, this research reveals the challenges and opportunities faced by Indonesia in implementing immigration policies related to the "One China Policy" and relations with Taiwan. The findings of this study are expected to provide a comprehensive understanding of the complex relationship between Indonesia, Taiwan, and the People's Republic of China, as well as its impact on Indonesia's immigration policies.